Question
Thu February 10, 2011 By: Sneha George

If the p th term of an AP is a and q th term is b then show that the sum of its first (p+q) terms is p+q/2[a+b+a-b/p+q][2p+1].

Expert Reply
Thu February 10, 2011
Dear student,
 

Let 'α' be the first term, and 'd' the common difference of the A.P..

Then,

T(n) = α + (n-1)d

S(n) = (n/2) [ 2α + (n-1) d ] ................. (1)


Now, given that : T(p) = a and T(q) = b.

∴ α + (p-1)d = a .......... (2)

α + (q-1)d = b .......... (3)

Subtracting (3) from (2),

 (p-q)d = (a-b)

∴ d = (a-b) / (p-q) ....................... (4)

Adding (2) and (3),

2α + (p+q-2)d = a + b

∴ [ 2α + (p+q-1)d ] - d = a + b

∴ [ 2α + (p+q-1)d ] = (a+b) + d

∴ from (4),

[ 2α + (p+q-1)d ] = (a+b) + (a-b)/(p-q) .......... (5)

Putting n = (p+q) in(1), and then using (5),

S(p+q) = [ (p+q)/2 ]· [ 2α + (p+q-1)d ]

           = [ (p+q)/2 ]· [ (a+b) + (a-b)/(p-q) ]

We hope that clarifies your query.

Regards,

Team

TopperLearning

Home Work Help